2019
DOI: 10.1136/bmjopen-2018-024199
|View full text |Cite
|
Sign up to set email alerts
|

Do data from child protective services and the police enhance modelling of perinatal risk for paediatric abusive head trauma? A retrospective case-control study

Abstract: ObjectivesFirst, to investigate whether there is a relationship between a family being known to child protective services or police at the time of birth and the risk of abusive head trauma (AHT, formerly known as shaken baby syndrome). Second, to investigate whether data from child protective services or police improve a predictive risk model derived from health records.DesignRetrospective case control study of child protective service and police records.SettingNine maternity hospitals.Participants142 consecut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Kelly et al shown in a retrospective case-control study that there´s a relationship between the fact of a family being known to child protective services or police at the time of birth and the risk of abusive head trauma. They pointed, however, that this data would add little predictive value to the risk assessment models of this type of trauma in the health services routine [41].…”
Section: Risk Factorsmentioning
confidence: 98%
“…Kelly et al shown in a retrospective case-control study that there´s a relationship between the fact of a family being known to child protective services or police at the time of birth and the risk of abusive head trauma. They pointed, however, that this data would add little predictive value to the risk assessment models of this type of trauma in the health services routine [41].…”
Section: Risk Factorsmentioning
confidence: 98%